Being a Teacher in the Age of AI: Between Technology, Values, and the Humanisation of Education - Farida, Ida (Journal of Islamic Studies and Civilization, 2025)
The rapid development of artificial intelligence (AI) has transformed education from a predominantly human-centred enterprise into a technologically mediated ecosystem that reshapes how knowledge is produced, distributed, and validated. This article examines the epistemological, ethical, and humanistic implications of AI’s growing influence on learning environments, drawing on philosophical perspectives and critical pedagogy. AI is increasingly functioning as an epistemic actor capable of predicting outcomes, personalising learning pathways, and making automated decisions, thereby shifting educational authority away from teachers and toward algorithmic systems. This shift raises profound questions about bias, privacy, social justice, and the normative purpose of education. Through an analysis of epistemic transformation, the reconceptualization of teacher roles, and emerging ethical challenges, the article argues for a humanistic framework that resists metric reductionism and reaffirms education as a project of liberation and human dignity. Teachers are positioned not merely as technology operators but as curators of knowledge, moral mediators, and critical agents who ensure that AI serves humane and democratic educational aims. The article concludes by offering a normative horizon for AI-integrated education and outlining future research directions for building ethically grounded, humanising educational ecosystems.